Ten days of levofloxacin-containing concomitant therapy can achieve effective Helicobacter pylori eradication in patients with type 2 diabetes. (18th August 2017) - Yang, Yao-Jong; Wu, Chung-Tai; Ou, Horng-Yih; Lin, Chin-Han; Cheng, Hsiu-Chi; Chang, Wei-Lun; Chen, Wei-Ying; Yang, Hsiao-Bai; Lu, Cheng-Chan; Sheu, Bor-Shyang
Abstract: Background: This study investigated whether levofloxacin-containing concomitant therapy can effectively eradicate Helicobacter pylori infection in patients with type 2 diabetes mellitus (T2DM). Methods: A total of 797 T2DM patients were screened for anti- H. pylori IgG antibodies, and the presence of H. pylori infection was confirmed by 13 C-urea breath test. We prospectively randomized 114 of these patients to receive either 10 d of levofloxacin-concomitant therapy (n = 55) or sequential therapy (n = 59). Antimicrobial resistance of H. pylori isolates collected from the patients with T2DM (n = 109) and dyspeptic controls without DM (n = 110) was determined using the E -test. This study was approved by our Institutional Review Board (A-BR-103-021). Results: The H. pylori eradication rates with concomitant therapy were higher than sequential therapy in both intention-to-treat (96.4% versus 81.4%, p = 0.012) and per-protocol (100% versus 85.4%, p = 0.006) analysis. The adverse effects in both groups were similarly mild. In the patients who received sequential therapy, clarithromycin resistance was significantly associated with eradication failure (p = 0.02). There were no significant differences in the antibiotic-resistant rates to amoxicillin, clarithromycin, metronidazole, tetracycline, and levofloxacin between the patients with and without T2DM. Conclusions: Ten days of levofloxacin-containing concomitant therapy is an effective and well-tolerated treatment to eradicate H. pylori infection for T2DM patients. Key messages: Ten days of levofloxacin-containing concomitant therapy is well tolerated and superior to clarithromycin-containing sequential therapy for first-line H. pylori eradication in patients with type 2 diabetes. Clarithromycin resistance to H. pylori is the main factor associated with eradication failure in clarithromycin-containing sequential therapy in diabetic patients.